(untitled) (Asian Journal of Ethnobiology, 2024)
Abstract. Mukarromah AN, Dzihni A, Azzam AK, Adiningsih AR, Utami AS, Nazar IA, Sunarto, Iskandar J, Saensouk S, Setyawan AD. 2024. Ethnobotany of traditional rituals of Javanese in the city of Surakarta, Central Java, Indonesia. Asian J Ethnobiol 7: 22-31. Surakarta is one of the municipalities in Central Java Province, Indonesia, known as a multicultural city, so it might be potential for cultural performances in the form of historical buildings, local culinary delights, cultural products, cultural arts, and traditional rituals. This research aimed to determine the use and meaning of plants in traditional rituals carried out by the people of Surakarta. Data were collected using in-depth interviews and observation methods collected primary data in three villages: Baluwarti, Mojosongo, and Keprabon, Surakarta City, Central Java, Indonesia. The results show that there are 10 traditional rituals commonly carried out by people in three villages, namely mitoni, medeking, procotan, wedding, death, grebeg maulud or sekaten, grebeg syawal, tedhak siten, tumpengan, and sadranan, where, each traditional ritual uses plants according to their respective meanings. There are 27 plant species belonging to 20 families used in traditional rituals by the people of three villages. Most respondents purchase plants used in traditional rituals from the traditional markets due to increasingly limited open space for planting the plant species.